Nikah Mut’ah di Iran dan Indonesia antara Regulasi dan Praktek - Fatah, Nasrul; Laili, Syarifah; Akbarizan, Akbarizan; Munir, Akmal Abdul (Universitas Batanghari Jambi, 2025)
This research aims to explore the rules and regulations of mut'ah marriage in Iran and Indonesia and analyze the practice in both countries. This research is library research using qualitative methods with a descriptive-analytic approach. The results of this research found that mut'ah marriages are officially regulated in marriage regulations in Iran, specifically in The Civil Code of The Islamic Republic of Iran 2000. These temporary marriages are recognized and equivalent to permanent marriages in general, and stipulate provisions that must be complied with in its implementation. However, in this modern era, the practice of mut'ah marriage in Iran is starting to be abandoned. In contrast to Indonesia, where there are no rules governing contract marriage law, it is not even recognized in regulations in Indonesia. However, in reality, the practice of contract marriage is increasingly common among Indonesian people.